Assessing the Impact of Corporate Governance and Strategic Leadership on Economic Growth and Market Stability - Kadim, Abdul; Yusnita, Irma; Sutarman, Asep; Lesmana, Rosa; Ramahdan, Fikri Arsla (Pandawan Sejahtera Indonesia, 2025)
In an increasingly complex and dynamic business environment, Corporate Governance and Strategic Leadership is the main factor in encouraging Economic Growth, Market Stability , and Organizational Performance. This study aims to evaluate the relationship between these variables and identify the role of strategic leadership and corporate governance in creating economic and market stability. This research uses the method Structural Equation Modeling based Partial Least Squares (PLS-SEM) by analyzing data from 100 participants ranging from middle level managers to senior executives. The research results show that Strategic Leadership has a significant positive influence on Economic Growth And Market Stability, whereas Corporate Governance actually shows a negative influence on these two variables. This could indicate underlying issues in the implementation of governance practices, such as lack of transparency, inefficiency in decision-making processes, or failure to address local market dynamics. Besides that, Market Stability has a greater impact on Organizational Performance compared with Economic Growth, which shows that market stability plays an important role in supporting organizational sustainability. Although this model provides strong empirical insight, value R-square A low level indicates that there are still other factors that need to be considered in improving organizational performance. As a future job (future work), this research recommends exploring additional variables such as technological innovation, government policy, as well as organizational culture factors to improve model predictions and expand understanding of the dynamics of economic growth and market stability.